2020
DOI: 10.3390/toxics9010003
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Biomass Smoke Exposure in Rats Produces Behavioral and Cognitive Alterations in the Offspring

Abstract: Particular concern at the present stage is the health effects of wildfires’ smoke. The aim of the study was to determine the impact of paternal biomass-smoke exposure on offspring’s behavior and cognitive abilities. Male rats were exposed to biomass smoke for four hours/day, five days/week, for four weeks. Average concentration of carbon monoxide and particulate matter of 2.5 μm PM2.5 in the chamber during exposure were 28.7 ± 5.3 mg/m3 and 1.9 ± 0.5 mg/m3, respectively. At the same time, high concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In these cases, a single lab might struggle to reproduce their own findings from one animal cohort to the next. Smoke exposure could also impact animal breeding operations including breeding success, fertility, and the health of the offspring [ 19 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, a single lab might struggle to reproduce their own findings from one animal cohort to the next. Smoke exposure could also impact animal breeding operations including breeding success, fertility, and the health of the offspring [ 19 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In primates, short-term perinatal exposure to wildfire smoke in California resulted in immune modulation that was observable into adolescence in the offspring [ 53 ]. Male rats exposed to wildfire smoke produce offspring with behavioral aberrancies, suggesting a potential for multi-generational effects [ 44 ]. Such effects could be passed through the germ line as we have demonstrated that prolonged exposure to wildfire smoke significantly alters the sperm epigenome of mice [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…emergency department visits and hospitalizations) to examine the relationship of acute wildfire exposures with respiratory and cardiovascular diagnoses (Alman et al, 2016;Cascio, 2018;Haikerwal et al, 2016;Hutchinson et al, 2018;Jia C. Liu, Pereira, Uhl, Bravo, & Bell, 2015). However research is limited for physiological systems beyond the respiratory and cardiovascular pathways (Chapters 12, 13), delayed health impacts from acute exposures (Orr, A. L. Migliaccio, Buford, Ballou, & Migliaccio, 2020), long-term morbidity (Schuller & Montrose, 2020;Sosedova et al, 2020), and assessment of effects from chronic, cumulative and mixtures of exposures. This research is expensive, complex and timeconsuming; but these studies are necessary to protect both public and occupational health.…”
Section: Future Research Needsmentioning
confidence: 99%
“…Experimental modeling of the impact of peat smoke was carried out in exposure chambers with a volume of 200 L. The smoke emitted from the smoke generator was directed into exposure chamber equipped with air temperature and humidity control devices, in which the animals were kept [19]. A fan was used to maintain a uniform flow of smoke into the breathing area of the animals.…”
Section: Exposure Studymentioning
confidence: 99%